Pengaruh Tingkat Pengangguran Terbuka Dan Indeks Pembangunan Manusia Terhadap Tingkat Kemiskinan Di Provinsi Jambi Tahun 2020-2024 - Ayub Afriansyah; Usdeldi Usdeldi; Habriyanto Habriyanto; Marissa Putriana; Eri Nofriza (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of the Human Development Index (HDI) and Open Unemployment Rate on the poverty level in Jambi Province during the period 2020–2024. The study focuses on the significant roles of HDI and open unemployment as factors in poverty alleviation efforts. The data used are secondary data obtained from the Central Bureau of Statistics (BPS) of Jambi Province for the specified period. This research employs a quantitative approach with panel data analysis processed using E-Views 13 software. The results show that partially, the open unemployment rate does not have a significant effect on poverty level, while HDI has a significant negative effect on poverty. Simultaneously, both HDI and open unemployment rate jointly have a significant influence on poverty level